Nursing Work Environment and Patient Outcomes in a Hospital Context: A Scoping Review. (May 2020) - Nascimento, Ana; Jesus, Élvio
Abstract : OBJECTIVE: The aims of this study were to summarize the current state of knowledge regarding the relationship between nursing work environment (NWE) and patient outcomes and to identify gaps in the literature. BACKGROUND: There was an increased awareness of the impact of NWE on patient outcomes, in particular, related to safety and quality of care. METHOD: Scoping review was conducted. Studies published between 2002 and the 1st quarter of 2018 were included to provide an overview of the research on the associations between NWE and patient outcomes. RESULTS: Of 2238 titles and abstracts identified, 35 studies were included, and publication ranged from 2005 to 2018. All studies included were observational, 4 had a longitudinal design, and the remaining studies were cross-sectional. Evidence indicates that better NWE decreases the risk of patient adverse events and increases the quality of care. CONCLUSIONS: The associations between different dimensions of NWE and patient outcomes should be explored. Abstract : Supplemental digital content is available in the text.